Establishing standardized conditions for clinically available sound-localization tests: A multicenter approach - Tadao Yoshida; Takashi Ishino; Satoshi Iwasaki; Naoki Oishi; Yusuke Matsuda; Tetsuya Tono; Kazuma Sugahara; Hiroshi Yamazaki; Sumito Jitsukawa; Hiroshi Nakanishi; Ryosuke Kitoh; Takashi Sato; et al. (PLoS ONE, 2025)
Sound localization is essential for auditory spatial awareness. The process relies on interaural differences in timing and level, and spectral cues. This study aimed to standardize sound-localization testing conditions across facilities in Japan, analyze the impact of early reflected sounds on localization accuracy, and compare outcomes between individuals with normal hearing and those with unilateral hearing loss. This study included 77 participants with normal hearing and 45 individuals with unilateral hearing loss, at 11 facilities. Sound-localization tests were conducted using nine loudspeakers arranged in a 180° horizontal arc. The stimuli consisted of Comité Consultatif International Téléphonique et Télégraphique (CCITT) and low-pass CCITT noise bursts at randomized levels of 50, 55, and 60 dB SPL. The reflected sound measurements employed time-stretched pulses to analyze early reflections (4–7 ms). The localization accuracy was assessed using the root-mean-square error and mean deviation score. Localization performance was negatively influenced by early reflections, with reflected sound envelope area and peak values within 4–7 ms correlating significantly with reduced accuracy (r = −0.535 to −0.555). Participants with normal hearing achieved a root-mean-square error of 2.0° ± 4.8°, whereas participants with unilateral hearing loss exhibited significantly greater errors (68.4° ± 40.7°, p < .001). Asymmetries in the left–right response accuracy correlated positively with the reflected sound characteristics (r > 0.6). Noise type (normal vs. low-pass CCITT) did not significantly impact performance in either group. Early reflections significantly compromise sound-localization accuracy, particularly in smaller testing environments where reflections overlap with direct sounds. Standardized testing protocols, in which early reflections are controlled, are critical for reliable assessments. The use of sound-absorbing materials can enhance the test precision, particularly in the clinical evaluation of unilateral hearing loss. These findings emphasize the need for optimizing acoustic conditions to improve the reliability and accuracy of sound-localization testing.